Hackathon fieldwork 2016 - Nick Taylor; Loraine Clarke (University of Dundee, 2018)
Fieldnotes and interviews from six hackathons attended as part of the "Hacking for Situated Civic Engagement" project. Further information about these events can be found in: Taylor, N. and Clarke, L.(2018). Everybody’s hacking: participation and the mainstreaming of hackathons. Proceedings of CHI 2018. Due to the wording of the ethics materials used, data can only be made to researchers. Further information about the conditions for access are available from the University of Dundee by writing to discovery@dundee.ac.uk
interviews and field notes